1
Solution:
2b + 5 = 7
Subtract 5 from both sides:
2b = 2
Divide by 2 on both sides:
b = 1
2b + 5 = 7
b =
9 answers
2z − 5 = 3
2z - 5 = 3
To solve for z, we need to isolate z on one side of the equation.
Add 5 to both sides:
2z = 3 + 5
2z = 8
Divide by 2 on both sides:
z = 8 / 2
z = 4
Therefore, z = 4.
To solve for z, we need to isolate z on one side of the equation.
Add 5 to both sides:
2z = 3 + 5
2z = 8
Divide by 2 on both sides:
z = 8 / 2
z = 4
Therefore, z = 4.
8 = 2g − 2
8 = 2g - 2
To solve for g, we need to isolate g on one side of the equation.
Add 2 to both sides:
8 + 2 = 2g - 2 + 2
10 = 2g
Divide by 2 on both sides:
10 / 2 = 2g / 2
5 = g
Therefore, g = 5.
To solve for g, we need to isolate g on one side of the equation.
Add 2 to both sides:
8 + 2 = 2g - 2 + 2
10 = 2g
Divide by 2 on both sides:
10 / 2 = 2g / 2
5 = g
Therefore, g = 5.
p/ 4 − 2 = 1 p =
To solve for p, we need to isolate p on one side of the equation.
Given: p/4 - 2 = 1
Add 2 to both sides:
p/4 = 1 + 2
p/4 = 3
Multiply by 4 on both sides to get rid of the fraction:
4 * (p/4) = 4 * 3
p = 12
Therefore, p = 12.
Given: p/4 - 2 = 1
Add 2 to both sides:
p/4 = 1 + 2
p/4 = 3
Multiply by 4 on both sides to get rid of the fraction:
4 * (p/4) = 4 * 3
p = 12
Therefore, p = 12.
4c + 3 = 19
c =
c =
To solve for c, we need to isolate c on one side of the equation.
Given: 4c + 3 = 19
Subtract 3 from both sides:
4c = 19 - 3
4c = 16
Divide by 4 on both sides:
c = 16 / 4
c = 4
Therefore, c = 4.
Given: 4c + 3 = 19
Subtract 3 from both sides:
4c = 19 - 3
4c = 16
Divide by 4 on both sides:
c = 16 / 4
c = 4
Therefore, c = 4.